A Viable System Approach to Tackle Complex Enterprise Situation for SISP - Ahmad, Rodina; B. Yusoff, Mohammed (Malaysian Journal of Computer Science, 2006)
Enterprise information model (EIM) development within Strategic Information System Planning (SISP) is crucial to provide comprehensive information requirements of the enterprise to assist in the accurate identification of Information System (IS) applications in order to realize the enterprise’s goals. One of the issues for the development of EIM is to understand, capture and represent core enterprise information requirements. This issue has been aggravated in a complex and uncertain enterprise situation in which multiple players are involved dynamically and they might have varying activities and expectations. This kind of situation demands an enhanced approach particularly in determining enterprise requirements and providing linkage for IS requirements identification. As the result, this research proposes an approach that uses Viable System Model (VSM) as an organizational instrument to facilitate the information determination process. Concepts from VSM, strategic context and enterprise systems are used as important dimensions for the proposed process. In brief, the approach was found to be useful as a means to elicit enterprise requirements and to provide structure to the development of an enterprise information model. It also offers several beneficial features such as inherent reengineering ability, multi-level analysis capability and prescriptive ability. , ,